Sugarcane mild mosaic virus: The rediscovery of an identified but unrecognized virus. (11th October 2022) - Mollov, Dimitre; Filloux, Denis; Grinstead, Samuel; Bolus, Stephen; Claude, Lisa; Fernandez, Emanuel; Julian, Charlotte; Candresse, Thierry; Lockhart, Ben; Roumagnac, Philippe; Rott, Philippe; Daugrois, Jean Heinrich
Abstract: The complete genome sequence of a previously uncharacterized sugarcane‐infecting virus of the genus Ampelovirus was obtained by high‐throughput sequencing (HTS) and rapid amplification of cDNA ends. This genome consists of 13, 114 nucleotides (nt) and harbours seven open reading frames. Phylogenetic and pairwise identity analyses with the complete or near‐complete genome sequences of 16 isolates revealed that they all belong to a new Ampelovirus species, family Closteroviridae . These 16 isolates were distributed in three phylogenetic groups and potential recombinant events were identified for only one of these isolates. An immunocapture‐reverse transcription‐PCR (IC‐RT‐PCR) assay was developed with antibodies previously produced against a clostero‐like virus that had not yet been recognized by the International Committee on Taxonomy of Viruses but for which the name sugarcane mild mosaic virus (SCMMV) had been proposed. The new ampelovirus was detected by IC‐RT‐PCR, and Sanger‐sequenced amplicons confirmed the identity of the virus based on HTS data. SCMMV was detected in 65 of 350 samples of quarantined sugarcane germplasm using RT‐PCR targeting the hsp70 gene. These samples originated from Africa, the Caribbean, North America, South America and South‐east Asia, thus revealing that SCMMV is present in many sugarcane‐growing regions of the world. The complete or near‐complete sequences reported here represent the first genomic sequences for SCMMV. Furthermore, the newly developed RT‐PCR diagnostic assay will facilitate the understanding of SCMMV epidemiology and will help improve management practices. Abstract : Sixteen isolates of sugarcane mild mosaic virus from Africa, Asia, and South and North America were completely sequenced, as genomic data and geographical distribution were previously not available.